Computational biomechanics of acute myocardial infarction and its treatment - Sirry, Mazin Salaheldin (Division of Cardiology, 2015)
The intramyocardial injection of biomaterials is an emerging therapy for myocardial infarction. Computational methods can help to study the mechanical effect s of biomaterial injectates on the infarcted heart s and can contribute to advance and optimise the concept of this therapy. The distribution of polyethylene glycol hydrogel injectate delivered immediately after the infarct induction was studied using rat infarct model. A micro-structural three-dimensional geometrical model of the entire injectate was reconstructed from histological micro graphs. The model provides a realistic representation of biomaterial injectates in computational models at macroscopic and microscopic level. Biaxial and compression mechanical testing was conducted for healing rat myocardial infarcted tissue at immediate (0 day), 7, 14 and 28 days after infarction onset. Infarcts were found to be mechanically anisotropic with the tissue being stiffer in circumferential direction than in longitudinal direction. The 0, 7, 14 and 28 days infarcts showed 443, 670, 857 and 1218 kPa circumferential tensile moduli. The 28 day infarct group showed a significantly higher compressive modulus compared to the other infarct groups (p= 0.0055, 0.028, and 0.018 for 0, 7 and 14 days groups). The biaxial mechanical data were utilized to establish material constitutive models of rat healing infarcts. Finite element model s and genetic algorithms were employed to identify the parameters of Fung orthotropic hyperelastic strain energy function for the healing infarcts. The provided infarct mechanical data and the identified constitutive parameters offer a platform for investigations of mechanical aspects of myocardial infarction and therapies in the rat, an experimental model extensively used in the development of infarct therapies. Micro-structurally detailed finite element model of a hydrogel injectate in an infarct was developed to provide an insight into the micromechanics of a hydrogel injectate and infarct during the diastolic filling. The injectate caused the end-diastolic fibre stresses in the infarct zone to decrease from 22.1 to 7.7 kPa in the 7 day infarct and from 35.7 to 9.7 kPa in the 28 day infarct. This stress reduction effect declined as the stiffness of the biomaterial increased. It is suggested that the gel works as a force attenuating system through micromechanical mechanisms reducing the force acting on tissue layers during the passive diastolic dilation of the left ventricle and thus reducing the stress induced in these tissue layers.